The circular economy and institutional change : transformation in theory and practice - Kaplan, Yilmaz (Routledge, 2026)
The climate crisis has emerged as a consequence of the linear economic system that developed in the aftermath of the Industrial Revolution. In recent years, global actors have recognised the need for institutional change from the linear economy to a more sustainable alternative: The circular economy.This book analyses the potential for transformative institutional change to a circular economy, both in theory and in practice. At the theoretical level, the book evaluates the feasibility of transitioning from a linear economy system to a circular economy by drawing on the principles of New Institutionalism. It thoroughly examines the key parameters of institutional change, focusing on the role of actors and new ideas within the institutional change process. Building upon this theoretical framework, the book then delves into the practical implementations of key actors. It first explores the role of the state and the market as crucial institutional actors, referencing the historical debate between these two entities. Additionally, the book critically assesses the agenda-setting power of influential international organisations, specifically the United Nations and the World Trade Organization, in driving a circular institutional change. Furthermore, it analyses the circular economy policies of influential global actors such as the European Union, China, Japan, and the USA. Aligned with these analyses, the book also examines the potential of a circular institutional change to bring about a paradigm shift from the prevailing industrial and consumer-centric society to an ecologically oriented society.This book is invaluable for readers interested in the circular economy, new institutionalism, the impacts of climate change, and alternative economic policy.
Keywords: Circular economy.; Organizational change -- Environmental aspects.; Organizational change -- Economic aspects.; elektronické knihy; electronic books